Evaluation of cover effects on bare stent mechanical response. (August 2016) - McGrath, D.J.; O'Brien, B.; Bruzzi, M.; Kelly, N.; Clauser, J.; Steinseifer, U.; McHugh, P.E.
Abstract: Covered tracheobronchial stents are used to prevent tumour growth from reoccluding the airways. In the present work a combination of experimental and computational methods are used to present the mechanical effects that adhered covers can have on stent performance. A prototype tracheobronchial stent is characterised in bare and covered configurations using radial force, flat plate and a novel non-uniform radial force test, while computational modelling is performed in parallel to extensively inform the physical testing. Results of the study show that cover configuration can have a significant structural effect on stent performance, and that stent response (bare or covered) is especially loading specific, highlighting that the loading configuration that a stent is about to be subjected to should be considered before stent implantation.